STRATEGI MENINGKATKAN PENDAPATAN PEDAGANG MUSLIM MELALUI USAHA PENJUALAN PAKET DATA - Raudatun Sumi; Zuhrinal M Nawawi (Universitas 45 Surabaya, 2023)
Trading activity is an activity that was previously practiced by the Prophet Muhammad SAW which is still being carried out by all mankind, starting from selling primary needs to luxury needs. To achieve the desired profit in the business world, it is necessary to carry out a strategy in practice, so that you can compete with other traders without having to do the wrong thing. As a trader, you don't just sell your wares, you need skills in managing finances and managing a good marketing system. This study aims to find out what strategies must be carried out by traders, especially Muslim traders to increase income from the previous one. The type of method used in this study is a qualitative method using two data collection techniques, namely literature study and observation.